2012
DOI: 10.1002/adfm.201202408
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Confinement on Microstructure and Charge Transport in High Performance Semicrystalline Polymer Semiconductors

Abstract: The film thickness of one of the most crystalline and highest performing polymer semiconductors, poly(2,5‐bis(3‐tetradecylthiophen‐2‐yl)thieno[3,2‐b]thiophene) (PBTTT), is varied in order to determine the effects of interfaces and confinement on the microstructure and performance in organic field effect transistors (OFETs). Crystalline texture and overall film crystallinity are found to depend strongly on film thickness and thermal processing. The angular distribution of crystallites narrows upon both a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
90
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 51 publications
5
90
1
Order By: Relevance
“…A number of studies have documented the trend of better crystalline texture resulting in improved electronic performance. 16,23,[46][47][48] Our data confirms and expands that structural details of semicrystalline polymers have an important role in controlling charge transport.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…A number of studies have documented the trend of better crystalline texture resulting in improved electronic performance. 16,23,[46][47][48] Our data confirms and expands that structural details of semicrystalline polymers have an important role in controlling charge transport.…”
Section: Resultssupporting
confidence: 81%
“…We have previously performed similar measurements in PBTTT, and found that crystallites exhibit comparable trends in texture as a function of thickness. 16 Similar to P3HT, mobility also drops sharply in extremely thin films due a suppression of overall film crystallinity, however PBTTT mobility also falls in thicker films. We have attributed this to the higher inherent crystallinity of PBTTT which causes the connections between crystalline grains, and hence film texture, to have a greater impact on charge carrier mobility.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Remarkably, x-ray diffraction (Fig. 4b) reveals that the width of the (020) diffraction peak related to the p-p stacking direction of P3HT chains is much narrower 43 in the P3HT/PS (5% P3HT) blend than in neat P3HT, implying a better order of P3HT chain in the PS matrix. Here the coherence length is B12 nm, as compared with B7 nm of neat P3HT.…”
Section: Resultsmentioning
confidence: 98%